A Novel Anti-HER2 Bispecific Antibody With Potent Tumor Inhibitory Effects In Vitro and In Vivo - Mohammadi, Mehdi; Jeddi-Tehrani, Mahmood; Golsaz-Shirazi, Forough; Arjmand, Mohammad; Bahadori, Tannaz; Judaki, Mohammad Ali; Shiravi, Fariba; Zare, Hengameh Ahmadi; Haghighat, Farzaneh Notash; Mobini, Maryam; Amiri, Mohammad Mehdi; Shokri, Fazel (Frontiers in Immunology, 2021)
Over expression of HER2 is reported in many types of cancer, which makes it a perfect candidate for targeted immunotherapy. Combination of two FDA approved monoclonal antibodies (mAbs), trastuzumab and pertuzumab, has more robust anti-tumor activity in patients with HER2-overexpressing breast cancer. Recently, we produced a new humanized anti-HER2 mAb, hersintuzumab, which recognizes a different epitope than trastuzumab and pertuzumab on HER2. This mAb in combination with trastuzumab exhibits more potent anti-tumor activity than each parental mAb alone. Here we have developed a novel bispecific anti-HER2 antibody (BsAb) designated as trasintuzumab, composed of trastuzumab and hersintuzumab, using dual variable domain immunoglobulin (DVD-Ig) technology. Both variable domains of trasintuzumab are fully functional and have similar affinities to the parental mAbs and are also able to bind to natural HER2 on surface of several HER2-expressing cell lines. Trasintuzumab was found to inhibit growth of different types of tumor cell lines through suppression of the AKT and ERK signaling pathways as efficiently as the combination of the parental mAbs. It also induced tumor regression as potently as the combination of the two mAbs in nude mice bearing ovarian and gastric cancer xenografts. Our data suggest that trasintuzumab may be a promising BsAb therapeutic candidate for treatment of HER2-overexpressing cancers.